Giving all energy stakeholders a voice: developing a theoretical framework for the uptake and sustained use of improved/clean biomass energy technologies - Robinson, Benjamin L (2021)
Achieving Sustainable Development Goal 7 - to ensure universal access to affordable, reliable and modern energy services by 2030 – represents a considerable challenge. Currently, 40% of the global population do not have access to sustainable energy sources, and instead rely on burning biomass (wood, dung, agricultural waste) to satisfy their energy needs. Despite a long history of energy technology for poverty-alleviation across the globe many interventions fail at persuading end-users to continue using such technologies beyond an initial adoption phase. Whilst many champion sustainable energy solutions, most implementation and evaluation approaches do not consider long term sustained use. As a result, many end-user-orientated energy solutions, such as Improved Cookstoves (ICS), fall out of use once project partners depart. These failures often reflect the fact that energy-focused development initiatives are shaped by increasingly complex technologies rather than social methodologies that prioritise understanding end-user priorities and the complex contextual barriers to sustained use.